Jeremia 1-25 - Maier, Christl (W. Kohlhammer GmbH, 2021)
This commentary regards Jer. 1&25 as a dramatic text: in laments, accusations, and predictions of disaster, it issues a polyphonic message on the downfall of Jerusalem and Judah. In accordance with the format of this series, the Hebrew text is initially analysed synchronically in relation to rhetoric, genre, linguistic phenomena, motifs, and theological statements. Against the background of the political situation of Judah from the end of the seventh century BCE, a diachronic analysis attempts to reconstruct the genesis of the text. The starting point for this is the older version of it, preserved in the Greek tradition. The texts, which are rich in imagery and sometimes disturbing, and which set the scene for the downfall of the kingdom of Judah, are interpreted by Maier for contemporary readers with the help of more recent hermeneutical viewpoints such as feminist biblical interpretation, postcolonial theory and trauma research.